Tourism Police Strategy in Maintaining the Security and Comfort of Foreign Tourists in Bali - Putra, I Komang Mahendra (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Bali is one of Indonesia's top tourist destinations, attracting millions of visitors annually. However, the increasing number of tourists also leads to higher security risks, such as pickpocketing, fraud, and other criminal activities. To address these challenges, tourism police play a strategic role in maintaining security and providing services to foreign tourists. This study aims to analyze the effectiveness of tourism police in Bali and identify the challenges they face. The research employs a qualitative descriptive approach, utilizing in-depth interviews, observations, and document analysis.The findings indicate that tourism police play a crucial role in enhancing tourism security; however, several obstacles persist, including limited human resources, insufficient foreign language training, and ineffective coordination with the tourism industry stakeholders. In conclusion, improving police training, investing in surveillance technology, and fostering stronger collaboration between law enforcement and tourism stakeholders are essential to creating a safer and more comfortable tourism environment.